Accelerated middle Miocene exhumation of the Talesh Mountains constrained by U‐Th/He thermochronometry: Evidence for the Arabia‐Eurasia collision in the NW Iranian Plateau. Issue 8 (16th August 2017) - Madanipour, Saeed; Ehlers, Todd A.; Yassaghi, Ali; Enkelmann, Eva
Abstract: The Talesh Mountains at the NW margin of the Iranian Plateau curve around the southwestern corner of the South Caspian Block and developed in response to the collision of the Arabian‐Eurasian Plates. The timing, rates, and regional changes in late Cenozoic deformation of the Talesh Mountains are not fully understood. In this study, we integrate 23 new apatite and zircon bedrock U‐Th/He ages and structurally restored geologic cross sections with previously published detrital apatite fission track data to reconstruct the deformation history of the Talesh Mountains. Our results reveal that slow rock exhumation initiated during the late Oligocene ( 27–23 Ma) and then accelerated in the middle Miocene ( 12 Ma). These events resulted in the present‐day high‐elevation and curved geometry of the mountains. The spatial and temporal distribution of cooling ages suggest that the Oligocene bending of the Talesh Mountains was earlier than in the eastern Alborz, Kopeh Dagh, and central Alborz Mountains that initiated during the late Cenozoic. Late Oligocene and middle Miocene deformation episodes recorded in the Talesh Mountains can be related to the collisional phases of the Arabian and Eurasian Plates. The lower rate of exhumation recorded in the Talesh Mountains occurred during the initial soft collision of the Arabian‐Eurasian Plates in the late Oligocene. The accelerated exhumation that occurred during final collision since the middle Miocene resulted from collision of the harder continental margin. Key Points: Late Cenozoic deformation in the Talesh Mountains initiated at late Oligocene (27–23 Ma) then accelerated during middle Miocene (12 Ma) Bending of the Talesh Mountains around the South Caspian Block starting in the late Oligocene and accelerated during middle Miocene Episodes of deformation recorded here for the Talesh Mountains attributed to the collisional phases of the Arabian and Eurasian Plates